Cognition and protest in democratic and authoritarian regimes, 1981–2020. (May 2022) - Lavrinenko, Olga
Whereas most theories of why the masses protest in democratic and authoritarian regimes involve some psychological or 'cognitive' element, major theories that include them (a) de-emphasize the structural conditions and (b) posit an explicit structure and cognition model but lack data to test its propositions across nations and time. This article synthesizes cognition-themed theories of democratic culture, political process theory's cognitive liberation, and the structural cognitive model's incentives. I test this synthetic theory in a specific way: that democratization and social spending interact with cognition in terms of external political efficacy and support for equitable economic redistribution to increase protest potential. I employ a three-level cross-national time-series model on the World Values Survey/European Values Study integrated dataset (1981–2020), consisting of democratic and authoritarian-leaning countries. I find that the three cognitive theories are complementary and that the interaction of structural changes with micro-level cognition has nuanced associations with protest potential.